The rise of Islamic extremism in Nigeria : an exploratory study with special focus on Boko Haram movement - Rufai, Saheed Ahmad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
There is a growing concern over the continued growth and proliferation of extremist Islamic movements in Nigeria in the last three decades. Notable among such movements are the Maitatsine Group, al-Zakzaky Group and, lately the Jama'at ahl-as-Sunnah li al-Da'wah wa al-Jihad (J.A.S.D.J) popularly known as Boko Haram, which is currently holding the Federal Government of Nigeria and all its security agencies, hostage. Of great concern is the fact that these and other extremist Islamic groups of similar nature, are of puritanical orientation. There however has not been a large-scale, comprehensive systematic research on the evolution, orientation and operations of such groups. The purpose of this study is to investigate the historical development of Islamic extremist movements in Nigeria from the outbreak of the Maitatsine Riot in 1980 to the ongoing Boko Haram rebellion in the country. Employing a combination of historical and analytical methods, the research is not only aimed at studying the historical development of the movements but also seeks to investigate the evolution of the idea of Islamic extremism, which has remained the hallmark of the movements being investigated. There is a preponderance of evidence for the need for a large-scale study which is capable of navigating a good direction for the government in its efforts at minimizing or eliminating the threat of the Islamic extremist groups in the country especially Boko Haram, This study is infact an attempt to fulfill the long-felt need for a chronological study on extremist Islamic movements in the sub-region. The study is significant in view of its potential to offer practical recommendations as an ameliorative proposal for the growing trend of extremism among today's Muslim revivalists.